Human resources practices and engagement of disability care front-line support workers - Del-Águila-Obra, Ana Rosa; Benítez-Saña, Rosa María; Padilla-Meléndez, Antonio (Emerald, 2025)
Purpose The topic of disability care non-profit organisations (NPOs) and human resource management (HRM) is relatively unexplored. From the job demand and resources theory, this research aims to study the impact of a high-performance work system (HPWS) on work engagement (WE) and determine which human resource (HR) practices have the most significant impact on WE in the case of disability care front-line support workers, named disability care workers onwards. Design/methodology/approach An empirical study with 264 participants from 145 Spanish disability care NPOs was conducted. Disability care workers’ perceptions about organisational HR practices and their impact on engagement were analysed using the partial least squares structural equation modelling method. The importance-performance matrix analysis (IPMA) was used to identify which HR practices were crucial in predicting engagement in this sector. Findings HPWS positively impacts engagement in the case of disability care workers. It was found that selection, teamwork and training are the most relevant HR practices in analysing engagement performance. Originality/value This paper contributes to the scarce literature about how people are managed in disability care NPOs. It provides theoretical insight and relevant managerial implications in an under-represented context. It is the first study showing the relationship between HR practices as antecedents of engagement in the case of disability care workers and identifying which practices are the most valuable. It provides disability care NPO HR managers with relevant practical keys.
Departamento de Organización de empresas y Marketing
Keywords: Recursos humanos; Gestión de personal; Organizaciones no lucrativas; Disability care front-line workers; Human resources management practices; Work engagement; Non-profit organisations